Revised age and stratigraphy of the classic Homo erectus-bearing succession at Trinil (Java, Indonesia). (1st February 2023) - L. Hilgen, Sander; Pop, Eduard; Adhityatama, Shinatria; A. Veldkamp, Tom; W.K. Berghuis, Harold; Sutisna, Indra; Yurnaldi, Dida; Dupont-Nivet, Guillaume; Reimann, Tony; Nowaczyk, Norbert; F. Kuiper, Klaudia; Krijgsman, Wout; et al.
Abstract: Obtaining accurate age control for fossils found on Java (Indonesia) has been and remains challenging due to geochronologic and stratigraphic uncertainties. In the 1890s, Dubois excavated numerous faunal fossils—including the first remains of Homo erectus —in sediments exposed along the Solo River at Trinil. Since then, various, and often contradictory age estimates have been proposed for the Trinil site and its fossils. However, the age of the fossil-bearing layers and the fossil assemblage remains inconclusive. This study constructs a chronostratigraphic framework for the Trinil site by documenting new stratigraphic sections and test pits, and by applying 40 Ar/ 39 Ar, paleomagnetic, and luminescence (pIRIR290 ) dating methods. Our study identifies two distinct, highly fossiliferous channel fills at the Trinil site. The stratigraphically lower Bone-Bearing Channel 1 (BBC-1) dates to 830–773 ka, while Bone-Bearing Channel 2 (BBC-2) is substantially younger with a maximum age of 450 ± 110 ka and an inferred minimum age of 430 ± 50 ka. Furthermore, significantly younger T2 terrace deposits are present at similar low elevations as BBC-1 and BBC-2. Our results demonstrate the presence of Early and Middle Pleistocene, and potentially even late Middle to Late Pleistocene fossiliferous sediments within the historical excavation area, suggesting that Dubois excavated fossils from at least three highly fossiliferous units with different ages. Moreover, evidence for reworking suggests that material found in the fossil-rich strata may originate from older deposits, introducing an additional source of temporal heterogeneity in the Trinil fossil assemblage. This challenges the current assumption that the Trinil H.K. fauna –which includes Homo erectus -is a homogeneous biostratigraphic unit. Furthermore, this scenario might explain why the Trinil skullcap collected by Dubois is tentatively grouped with Homo erectus fossils from Early Pleistocene sediments at Sangiran, while Trinil Femur I shares affinities with hominin fossils of Late Pleistocene age. Highlights: A revised chronostratigraphic framework is presented for the Trinil site. Early to Late Pleistocene fossiliferous deposits are found at the same elevation. Dubois' bonebed likely consists of two layers dated at 830–773 and 560–380 ka. They are cut by upper Middle to Upper Pleistocene fossiliferous terrace deposits. These findings challenge the Trinil H.K. faunal unit that includes Homo erectus.